Mining and the conflict over values in Nusa Tenggara Timur Province, Eastern Indonesia. Issue 2 (April 2016) - Erb, Maribeth
Abstract: Political reform in Indonesia, which began in 1999, opened up spaces for local governments to make more decisions that would affect the economic development of their districts. With the freedom to seek foreign investment, many district heads in Nusa Tenggara Timur province began to allocate mining licenses for mineral exploration. This proliferation of mining activity increasingly received a lot of resistance from environmental NGOs, church organizations and various communities across the province, and became a catalyst for people to rethink development strategies and values that are thought to be associated with various livelihoods. In this paper I examine the conflict over various values, such as justice, democracy, sustainability, environmental conservation and cultural tradition, which I look at through a series of cases that trace the recent history of mining in this eastern Indonesian province. Building on critiques of the simplistic contrast between unsustainable versus sustainable development, focussing on reputed differences between mining and tourism, I examine these two industries, following Büscher and Davidov, (2014a, 2014b) as forming a type of "nexus". This nexus I argue is what has instigated this examination of values.